EFFECTIVE METHODS OF TEACHING THE JAPANESE LANGUAGE - Л.Д. Нурсеитовa (Journal of Oriental Studies, 2019)
This article describes the main stages and approaches to teaching Japanese as a foreign language. Japanese language teaching is growing throughout the world. It is important that this growth is not only quantitative but also qualitative in establishing new patterns for Japanese language instruction. Methods of teaching Japanese language are divided into the following types: grammatical introduction, basic and practical exercises. These basic techniques are being used in explaining new material. Key words: methods, grammatical introduction, practical exercises, motivation, effective, commu- nicative method.